Seeking culture in a cultural void? the relationship between suburbia and popular culture (2013)
Th ere are some concepts that lend themselves to watertight defi nition. We know that a recession is when an economy has experienced two quarters of negative growth and there is a clear formula for calculating gross domestic product (GDP) but by contrast we are not so clear on what exactly it is that unambiguously a ‘suburb’ may or may not be. Its derivative ‘suburbia’ also eludes easy defi nition notwithstanding that both are long established terms. Th e Compact Edition of the Oxford English Dictionary tells us that the origins and usage of the word ‘suburb’ go way back at least to Chaucer. Many of us have some sort of inklings about what this peculiarly Anglo-Saxon/Anglophone/Anglo-American notion is but there is no common agreement on what constitutes it. In the absence of any defi nitive defi nition of what we mean by suburbia, the concept has frequently formed in the popular imagination through representations of it in popular culture.